Rattus hoogerwerfi Chasen 1939 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
680. Hoogerwert’s Sumatran Rat Rattus hoogerwerfi French: Rat de Hoogerwef / German: Hoogerwerf-Ratte / Spanish: Rata de Sumatra de Hoogerwerf Other common names: Atjehan Moutain Rat, Hoogerwerf’s Rat Taxonomy. Rattus hoogerwerfi Chasen, 1939, Blang Kedjeren, 2900 ft (= 885 m), Gunung [euser, Aceh, western Sumatra, Indonesia. Phylogenetic placement of R. hoogerwerfi in Rattus is uncertain, although it might be related to R. korinchi and R. baluensis. Monotypic. Distribution. Highlands of Mt Leuser, NW Sumatra. Descriptive notes. Head-body 165-196 mm, tail 210-257 mm, ear 19-26 mm, hindfoot 36-39 mm; weight 113-153 g. Hoogerwerf’s Sumatran Rat is medium-sized and distinctive, with very soft and long pelage. Dorsum is dark ocherous buffish brown, with many black guard hairs and gray underfur, lighter on sides and blending into ventral pelage. Venteris rufous buff. Juveniles are dullerbrown in color. Feet are thinly covered in short dark brown hair, with silvery hairs around bases of claws. Ears are brown; vibrissae are long and black. Tail is ¢.130% of head-body length, dark brown for basal one-half, and white for distal one-half. Skull is gracile and flat. There are four pairs of mammae: one post-axillary, one abdominal, and two inguinal. Habitat. Upper montane moss forest and exposed forested heath at elevations of 2500-3000 m. Food and Feeding. No information. Breeding. No information. Activity patterns. No information. Movements, Home range and Social organization. No information. Status and Conservation. Classified as Vulnerable on The IUCN Red List. There are no known threats to Hoogerwerf’s Sumatran Rat, but habitat loss and destruction potentially affect it. It is found in Gunung Leuser National Park and might be more widely distributed in western Sumatra. Additional research is needed to fully understand its distribution, natural history, taxonomy, and conservation threats. Bibliography. Clayton (2016e), Miller (1942), Musser & Carleton (2005), Musser & Newcomb (1983). Published as part of Don ...